F64. EXPLORING THE ROLE OF EMOTION DYSREGULATION AND IMPULSIVITY ON SUICIDAL IDEATION AND BEHAVIOR WITHIN AN EARLY PSYCHOSIS POPULATION. (9th April 2019) - Grattan, Rebecca; Tully, Laura; Lesh, Tyler; Carter, Cameron; Niendam, Tara
Abstract: Background: Suicide is a leading cause of death for young people and a challenging clinical issue across diagnostic categories. Historically suicide research has focused on specific diagnostic groups, rather than transdiagnostic risk factors. This has hindered prevention efforts and early identification of those at risk. Emotion dysregulation and impulsivity represent two transdiagnostic risk factors for suicide. While these constructs are often investigated separately, we hypothesized that emotion dysregulation and impulsivity cluster together, and that this combination increases suicidal behavior and ideation. This hypothesis was examined in an early psychosis population, a group at increased risk for suicide, comprised of affective and non-affective diagnoses. Methods: Participants were recruited from an Early Psychosis Program (n= 245, ages 12–37, 72% male). Clinician ratings of symptoms (Brief Psychiatric Rating Scale; BPRS) and history of suicidal ideation, behavior and non-suicidal self-injurious behavior (NSSIB; Columbia-Suicide Severity Rating Scale) were obtained at baseline and 12 month follow up. A subset (n= 78, ages 12–32, 62% male) completed self-report measures of emotion dysregulation (subset from Wender Utah Rating Scale) and impulsivity (Barrett Impulsiveness Scale). Regression analyses examined whether emotion dysregulation and impulsivity individually predicted suicidal behavior and ideation at baseline and follow up. Hierarchical cluster analyses of emotion dysregulation and impulsivity detected two distinct groups, and suicide variables were compared across groups. Results: In the full sample (N = 245), 52% reported a history of suicidal ideation, 22% reported suicidal behavior and 18% reported NSSIB. In the subset, emotion dysregulation predicted history of suicidal ideation (R2 = .07, F (1, 83) = 6.17, p = .02), behavior (R2 = .20, F (1, 83) = 21.2, p < .01) and NSSIB (p = .05). When controlling for BPRS score, only the relationship with behavior remained significant. Attention impulsivity scores predicted suicidal ideation (R2 = .55, F (1, 127) = 7.34, p = .01) and NSSIB (p = .04) but these were not significant when controlling for BPRS score. Motor and planning impulsivity scores were not related to suicidal ideation, behavior or NSSIB. Cluster analysis identified two groups: an emotionally dysregulated group with high impulsivity and inattention (N = 10), and a more regulated, less impulsive group (N = 68). The dysregulated group reported a history of higher ideation (R2 = .07, F (1, 69) = 5.43, p = .02), suicidal behavior (R2 = .28, F (1, 69) = 27.2, p < .01) and NSSIB (p = .04). Again, only the relationship with behavior remained significant controlling for BPRS score. In a preliminary outcome analysis, 122 individuals completed 12-month follow up, with 37% reporting ideation and 7% reporting suicidal behavior since baseline. History of depression, impulsivity, ideation and behavior did not predict 12-month ideation or behavior. Emotion dysregulation at baseline predicted suicidal behavior (R2 = .50, F (2, 40) = 4.32, p < .01) but not ideation at 12 months. Discussion: Emotion dysregulation and impulsivity clustered together and high scores on both indicated past suicidal behavior, ideation and NSSIB. However, only the relationship with behavior was significant when accounting for psychiatric symptoms. Emotion dysregulation was the best predictor of behavior over 12 months. This suggests emotion dysregulation is a potential target for suicide prevention in early psychosis. Future directions include examining sex differences and using more targeted measures of emotion dysregulation to further distinguish the roles of impulsivity and emotion dysregulation on suicidal behavior.